Analisis Inflasi Terhadap Pertumbuhan Ekonomi Di Indonesia - Fitria Salsabilla (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Developing countries tend to experience inflation, countries with inflation rates of less than 3% are still achieving normal standards, while countries with high and unstable inflation experience economic instability. increase in prospects. A general and continuous decline in the price level of goods and services in a country leads to higher levels of poverty and unemployment. This study uses quantitative methods using time series data collected between 2016 and 2020 and statistical calculations using SPSS. The results showed that the inflation rate was 3.532> t table 2.306 and the significance level was 0.039 < . 0.05, which means that inflation affects Indonesia's economic growth / Growth Domestic Product (GDP).